OH2 oncolytic virus inhibits non-small-cell lung cancer metastasis via β-catenin pathway suppression - Han Hu; Qi Shen; Lingfang Zhang; Shuaiqi Zhu; Yining Cheng; Haixiao Duan; Fan Zhang; Lin Wang; Yuling Jin; Jinjin Cao; Yang Wang; Binlei Liu (Communications Biology)
Abstract The five-year survival rate for non-small-cell lung cancer (NSCLC) remains poor, primarily due to tumor invasion and metastasis. This study evaluates the anti-metastatic potential of the oncolytic virus OH2 in NSCLC. OH2 inhibits migration and invasion of NSCLC by downregulating β-catenin, as demonstrated in vitro and in a lung metastasis model. OH2 reduces β-catenin mRNA levels, suppressing its transcriptional activity and downstream expression of Matrix Metalloproteinases (MMPs), key mediators of extracellular matrix degradation. Proteomic analysis of the secretome confirms reduced MMPs expression following OH2 treatment. Mechanistically, the OH2 tegument protein UL41 is identified as a critical factor that degrades β-catenin mRNA, thus inhibiting β-catenin nuclear transcriptional activity. These findings reveal a novel anti-metastatic mechanism of OH2 via disruption of the β-catenin/MMPs axis and support its potential as a therapeutic candidate for invasive NSCLC.